2D/2d heterojunction of MoS2/g-C3N4 nanoflowers for enhanced visible-light-driven photocatalytic and electrochemical degradation of organic pollutants. (15th November 2020) - Monga, Divya; Ilager, Davalasab; Shetti, Nagaraj P.; Basu, Soumen; Aminabhavi, Tejraj M.
Abstract: Photodegradation of toxic pollutants is a promising approach to deal with wastewater management. In this regard, MoS2 /g-C3 N4 (MSC) derived composites with varying weight-ratios were prepared via fast (30 min) one step microwave-assisted method. The materials were characterized by XRD, XPS, EDS, FESEM and HRTEM to validate their flower-like and sheet-like morphologies. The PL and UV–vis DRS spectra exhibited low recombination-rate and band-gap (1.7 eV), which is appropriate for an effective visible-light degradation. Photocatalytic performance of the catalysts was analyzed by investigating the degradation of methylene blue (MB) as well as pesticide fipronil. Best results were obtained by 5:1 MSC (98.7% degradation efficacy; rate constant 0.0261 min −1 ) in 80 min under the sunlight. The effects of solution pH, catalyst-dose, scavengers and illumination-area were also explored. The catalyst was reusable as confirmed by degradation studies ( 82% efficiency) even after 5-cycles. The photocatalytic treatment of real industrial-wastewater was also conducted. The TOC and COD analysis validated that the treatment by as-prepared catalyst is more proficient for effluent-treatment than the industrial physico-chemical treatments. Electrochemical degradation of MB was also investigated using the glassy carbon electrode modified with different MSC-ratios. The electrode modified with 5:1 MSC at pH 7 manifested the maximum peak current. The plausible mechanisms for photocatalytic and electrochemical degradations were proposed, which suggested the remarkable potential the prepared nanocomposites for wastewater treatment. Graphical abstract: Image 1 Highlights: MoS2 /g-C3 N4 composites with different weight ratio were synthesized by microwave method. Visible light active nanocomposites are highly effective for toxic pollutant degradation. Degradation efficiency was remarkably affected by the amount of MoS2 and g-C3 N4 . Electrochemical degradation of MB was studied using MoS2 /g-C3 N4 modified GCE. COD and TOC analysis of real wastewater confirm the efficiency of the catalysts.